The radiological features, diagnosis and management of screen-detected lobular neoplasia of the breast: Findings from the Sloane Project. (June 2016) - Maxwell, Anthony J.; Clements, Karen; Dodwell, David J.; Evans, Andrew J.; Francis, Adele; Hussain, Monuwar; Morris, Julie; Pinder, Sarah E.; Sawyer, Elinor J.; Thomas, Jeremy; Thompson, Alastair; ,
Abstract: Objectives: To investigate the radiological features, diagnosis and management of screen-detected lobular neoplasia (LN) of the breast. Materials and methods: 392 women with pure LN alone were identified within the prospective UK cohort study of screen-detected non-invasive breast neoplasia (the Sloane Project). Demography, radiological features and diagnostic and therapeutic procedures were analysed. Results: Non-pleomorphic LN (369/392) was most frequently diagnosed among women aged 50–54 and in 53.5% was at the first screen. It occurred most commonly on the left (58.0%; p = 0.003), in the upper outer quadrant and confined to one site (single quadrant or retroareolar region). No bilateral cases were found. The predominant radiological feature was microcalcification (most commonly granular) which increased in frequency with increasing breast density. Casting microcalcification as a predominant feature had a significantly higher lesion size compared to granular and punctate patterns (p = 0.034). 326/369 (88.3%) women underwent surgery, including 17 who underwent >1 operation, six who had mastectomy and six who had axillary surgery. Two patients had radiotherapy and 15 had endocrine treatment. Pleomorphic lobular carcinoma in situ (23/392) presented as granular microcalcification in 12; four women had mastectomy and six had radiotherapy. Conclusion: Screen-detected LN occurs in relatively young women and is predominantly non-pleomorphic and unilateral. It is typically associated with granular or punctate microcalcification in the left upper outer quadrant. Management, including surgical resection, is highly variable and requires evidence-based guideline development. Highlights: Non-pleomorphic lobular neoplasia is typically left-sided and unilateral. In many cases it develops before the menopause. It is commonly associated with granular microcalcification Management is highly variable and surgical treatment often excessive. Evidence-based management guidelines are required.